Phonemic and semantic fluency among individuals diagnosed with MCI, AD, and other dementias - Kristín Birna Júlíudóttir 2001- (2023)
Verbal fluency tests that are used in neuropsychological assessment are usually twofold: Phonemic and semantic fluency tasks. This study aimed to examine performance differences in phonemic and semantic fluency tasks among individuals diagnosed with mild cognitive impairment (MCI), Alzheimer’s dementia, and other dementias. Semantic memory is commonly affected early in Alzheimer’s dementia, and there is evidence that also applies to the type of MCI that has an increased risk of developing Alzheimer’s dementia. Therefore, performance on semantic fluency tasks can possibly be used to predict if an individual is likely to develop dementia after being diagnosed with MCI. It was hypothesized that performance on the semantic fluency task would be significantly worse than performance on the phonemic fluency task among individuals with Alzheimer’s dementia and amnestic MCI, which is the type of MCI that has an increased risk of Alzheimer’s dementia. This study was archival and based on reviewing existing data from the Memory Clinic at Landakot at the Landspitali – The National University Hospital of Iceland from 2015-2020. The results of this study showed that the Alzheimer’s group performed significantly worse on the semantic fluency task than on the phonemic fluency task. There was no significant difference between tasks in the amnestic MCI group. However, they performed slightly worse on the semantic task, indicating similar patterns to Alzheimer’s dementia. Keywords: Verbal fluency, phonemic fluency, semantic fluency, mild cognitive impairment, Alzheimer’s dementia. Orðaflæðispróf sem eru gjarnan notuð í taugasálfræðilegu mati samanstanda almennt af hljóðungaflæði og merkingarflæði. Markmið þessarar rannsóknar var að meta frammistöðumun á hljóðunga- og merkingarflæði meðal einstaklinga sem greinast með væga vitræna skerðingu (MCI), Alzheimer heilabilun eða aðra tegund heilabilunar. Merkingarminni skerðist oft snemma í Alzheimer heilabilun og eru vísbendingar um að það eigi einnig við um þá tegund MCI sem hefur ...